2016
DOI: 10.3390/soc6020017
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated with Teen Pregnancy in Vietnam: Results from Two National Surveys

Abstract: This study asked two broad questions: (1) show that the prevalence of pregnancy among Vietnamese teenagers in the surveys was stable at 4%, or 40 pregnancies per 1000 adolescent girls aged 14 to 19. Age, experience of domestic violence, and early sexual debut were positively correlated with higher odds of teenage pregnancy for both survey cohorts; however, being an ethnic minority, educational attainment, sexual education at school, Internet use, and depressive symptoms were significantly related to teenage p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 13 publications
3
23
2
2
Order By: Relevance
“…Mutanana's (2015) study, showed contributing factors to teenage pregnancy in rural communities from Zimbabwe is socio-economic background, and low levels of education. Nguyen (2016), stated in his research the variables of education level, and sexual education in schools are significantly related to teenage pregnancy. This is not in accordance with the results of this study which indicated that education level is not related to teen pregnancy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutanana's (2015) study, showed contributing factors to teenage pregnancy in rural communities from Zimbabwe is socio-economic background, and low levels of education. Nguyen (2016), stated in his research the variables of education level, and sexual education in schools are significantly related to teenage pregnancy. This is not in accordance with the results of this study which indicated that education level is not related to teen pregnancy.…”
Section: Resultsmentioning
confidence: 99%
“…Mutanana's (2015) study, showed contributing factors to teenage pregnancy in rural communities from Zimbabwe were the influence of peers, lack of sex education, no use of contraceptives, tradition, and low selfesteem. Nguyen (2016), stated in his research that the prevalence of teen pregnancies in Vietnam were women aged 14 to 19, and variables that were positively correlated were age, experience of domestic violence and early sexual behavior. Van Eijk (2015), said that the problem of teen pregnancy was an important issue in The result of this study shows no correlation between educational background (1.00), marital status (0.077), and parenting with teen pregnancy (0.438).…”
Section: Resultsmentioning
confidence: 99%
“…Beberapa komplikasi yang terjadi pada kehamilan usia muda antara lain berisiko kelahiran prematur, berat badan lahir rendah (BBLR), perdarahan persalinan yang dapat meningkatkan kematian ibu dan bayi. Kehamilan usia remaja juga terkait dengan kehamilan yang tidak dikehendaki dan aborsi (Nguyen, 2016;Sarantaki, 2014).…”
Section: Pendahuluanunclassified
“…Kehamilan yang tidak diinginkan merupakan salah satu pemicu munculnya depresi (Nguyen, 2016). Masa childbearing pada usia remaja merupakan resiko tinggi akan depresi, kekerasan dan komplikasi (Barnet et al, 2008).…”
Section: Pendahuluanunclassified
“…Moreover, babies of adolescent mothers are more likely to be stillborn with low Apgar score, die early, or with long term health challenges. Adolescents who become pregnant while schooling are at risk of abridged education, and thus limited career prospects (8) (9). To complement health education, there is a need for routine assessment of adolescent predisposing factors.…”
Section: Introductionmentioning
confidence: 99%